2015
DOI: 10.1002/jssc.201500212
|View full text |Cite
|
Sign up to set email alerts
|

Resorcinol–formaldehyde xerogel as a micro‐solid‐phase extraction sorbent for the determination of herbicides in aquatic environmental samples

Abstract: In this study, organic aerogels were synthesized by the sol-gel polycondensation of mixed cresol with formaldehyde in a slightly basic aqueous solution. Carbon aerogels and xerogels are generated by pyrolysis of organic aerogels. The novel sol-gel-based micro-solid-phase extraction sorbent, resorcinol-formaldehyde xerogel, was employed for preconcentration of some selected herbicides. Three herbicides of the aryloxyphenoxypropionate group, clodinafop-propargyl, haloxyfop-etotyl, and fenoxaprop-P-ethyl, were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, these materials are characterized by having high porosity and surface area, controllable pore size, and also having the possibility of being shaped as desired 22 , 23 . These attributes make CXs attractive materials for several applications, including fuel cells 24 , 25 , catalysis 26 – 28 and adsorption for both water treatment 29 , 30 or analytical chemistry 31 , 32 . Regarding water treatment by adsorption, some authors have been studying CXs for removal of specific PSs and CECs: (i) Moral-Rodriguez et al 33 studied different CXs for the adsorption of diclofenac; (ii) Álvarez et al 34 applied CXs as adsorbents for the removal of caffeine and diclofenac; and (iii) Carabineiro et al 35 studied the adsorption capacity of CXs for the antibiotic ciprofloxacin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these materials are characterized by having high porosity and surface area, controllable pore size, and also having the possibility of being shaped as desired 22 , 23 . These attributes make CXs attractive materials for several applications, including fuel cells 24 , 25 , catalysis 26 – 28 and adsorption for both water treatment 29 , 30 or analytical chemistry 31 , 32 . Regarding water treatment by adsorption, some authors have been studying CXs for removal of specific PSs and CECs: (i) Moral-Rodriguez et al 33 studied different CXs for the adsorption of diclofenac; (ii) Álvarez et al 34 applied CXs as adsorbents for the removal of caffeine and diclofenac; and (iii) Carabineiro et al 35 studied the adsorption capacity of CXs for the antibiotic ciprofloxacin.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding water treatment by adsorption, some authors have been studying CXs for removal of specific PSs and CECs: (i) Moral-Rodriguez et al 33 studied different CXs for the adsorption of diclofenac; (ii) Álvarez et al 34 applied CXs as adsorbents for the removal of caffeine and diclofenac; and (iii) Carabineiro et al 35 studied the adsorption capacity of CXs for the antibiotic ciprofloxacin. In the field of analytical chemistry, only two studies were found in the literature for the analysis of pollutants by using CXs in SPE: (i) one to determine the effectiveness of an oxidized CX material as sorbent in SPE to preconcentrate lead from tap water samples 32 ; and (ii) another to extract aryloxyphenoxypropionate herbicides from aquatic environmental samples by micro-SPE 31 . However, studies focused on the application of CXs as SPE adsorbent for extraction of other PSs 2 or CECs listed in the Watch List of the EU Decisions 3 – 5 were not found.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the unique advantages, different kind of aerogels have been developed and applied to many fields . Silica aerogels , graphene aerogels , and carbon aerogels were developed for SPME or SPE. Our group prepared an organic hybrid silica aerogel and an ionic liquid‐functionalized silica aerogel as the coatings for fiber SPME, and also produced melamine–formaldehyde aerogel , ionic liquid modified melamine–formaldehyde aerogel , and organic–inorganic hybrid silica aerogel for in‐tube SPME sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike ELISA, the latter two methods utilize instruments that are not commonplace across feed/food safety or toxicology laboratories. For laboratories that lack LC/MS instruments, a commonly utilized method for haloxyfop detection is gas chromatography/mass spectrometry (GC/MS) which has been applied to fruits, vegetables, aquatic environmental samples and in basic chemical research studies conducted since the 1980s 17–19 . While GC/MS with capillary chromatography has excellent capabilities for chromatographic separability and sensitivity along with numerous mass spectral libraries for unknowns matching, it suffers from problems in specificity in complex matrices with their high potential for overlapping compounds.…”
Section: Introductionmentioning
confidence: 99%